PENGUJIAN EFEKTIFITAS FORMULA GEL EKSTRAK DAUN BELUNTAS (Pluchea indica (L.) Less) DENGAN VARIASI KONSENTRASI GELLING AGENT SEBAGAI KANDIDAT SEDIAAN ANTI JERAWAT - Andi Ulfah Magefirah Rasyid; Zahira Amody (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Beluntas (Pluchea indica (L.) Less) is a plant that is often used in traditional medicine because of the presence of several substances that have activity as antimicrobial compounds. Beluntas leaves contain secondary metabolite compounds such as flavonoids, alkaloids, tannins, steroids, terpenoids and saponins which can function as antibacterial. This experimental research aimed at obtaining beluntas leaf extract gel and to determine the physical stability and the effectiveness of beluntas extract gel against Propionibacterium acnes. The first step is drying the beluntas leaves and and extracted by maceration method with 70% ethanol solvent. The extract obtained was then formulated into a gel and evaluated, the evaluation results show that formula 1 is the most stable. The results showed that beluntas leaf extract gel was effective in inhibiting the growth of Propionibacterium acnes, the inhibition zone obtained was categorized as strong, where the average diameter before the accelerated stability test was 12.02 mm and 11.58 mm after the accelerated stability test.